(untitled) (American International Journal of Business and Management Studies, 2021)
The aim of this study is to examine the effects individual attributes on the Employability Readiness among engineering graduates of the High Education Institutes in Oman. The study adopted self-directed structured questionnaire which was distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used the structural equation modelling (SEM) for analysing the collected data. The findings of the statistical analysis of the study showed the most influential individual attributes on graduates’ readiness for employability are workshop attendance that affect the attainment of the technical skills of the graduates, family motivations, and graduates’ career orientations that help graduates to identify future career requirements and future career opportunities, and graduates’ personal learning targets. Also, class attendance, academic excellence, financial sources, and parents’ career position showed high important effects as well. The findings of this attribute which consist of the individual attributes of personnel’s’ values, attitudes, abilities, and work-life balance enhance the graduates attainment of the adaptability and flexibility attributes for their future readiness for employability. Therefore, study findings showed Individual attributes factor has high influence on the Readiness for Employability of the graduates in Oman. Finally, the study’s implementations and recommendations could be transferred to the Gulf and Arab or other countries’ contexts having similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.